Revisiting Stoker’s Dracula: No Brave Good Villains Left - Ferreira de Castro, Carla (2015)
This article considers the implication of the main character, Count Dracula, the villain/anti-hero in Stoker’s text, as a starting point to analysing the approaches deployed in the novel that introduce new stratagems to uncover the motives which allow the readers to find excuses to deny “pure” evilness. Stoker’s Dracula (1897) introduced the plausibility―in the realm of the gothic horror novel―of finding heroes in modern day “villains”. This paper will argue this influence by introducing connections with modern “pop” vampires: from the teenage vampires in the Twilight saga both the texts (2005, 2006, 2007, & 2008) and the film versions ( 2008, 2009, 2010, & 2012), to the grown-up fantasies of Charlaine Harris in the True Blood saga (both the 13 books published between 2001 and 2012 and the Home Box Office TV series that started in 2008 and, so far is in its 7th season in 2014) and Tim Burton’s Dark Shadows (2012), the remake of the 70s American Broadcasting Company Gothic soap opera (which ran between june 1966 to April 1977). Bearing in mind the history of the vampire, through a brief account of its constant presence in the contemporary film and television industry, we will attempt to unveil the cultural reasons that bring light to the fact that modern society is out of brave good villains. The presentation will retrieve some theoretical support from Cristopher Frayling’s analysis of the vampire myth, David Punters’ ideas on the modern gothic and Maggie Kilgour’s assumptions on the rise of the gothic.